2019
DOI: 10.2176/nmc.oa.2018-0309
|View full text |Cite
|
Sign up to set email alerts
|

A Single-center Retrospective Study with 5- and 10-year Follow-up of Carotid Endarterectomy with Patch Graft

Abstract: Carotid endarterectomy (CEA) is widely used for cervical artery stenosis. In Japan, primary closure after endarterectomy has been a standard technique. Recently, the patch closure has been shown to be superior to the primary suture for the prevention of restenosis and ipsilateral stroke. This study evaluated the 5- and 10-year outcomes following CEA with patch graft closure in our institution. Between January 2000 and March 2013, 134 patients, who underwent CEA with patch graft closure were investigated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that approximately 5-15% of patients with carotid artery stenosis experience restenosis following CEA. 4,5 Although the detailed mechanisms are yet to be determined, it is generally believed that the pathological proliferation and inflammatory responses of vascular smooth muscle cells (VSMCs) can potentially contribute to atherosclerosis and arterial restenosis. 6,7 Therefore, the inhibition of the proliferation of VSMCs and the reduction of the occurrence of restenosis following CEA has become a major research focus.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that approximately 5-15% of patients with carotid artery stenosis experience restenosis following CEA. 4,5 Although the detailed mechanisms are yet to be determined, it is generally believed that the pathological proliferation and inflammatory responses of vascular smooth muscle cells (VSMCs) can potentially contribute to atherosclerosis and arterial restenosis. 6,7 Therefore, the inhibition of the proliferation of VSMCs and the reduction of the occurrence of restenosis following CEA has become a major research focus.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the need for antiplatelet therapy in the perioperative period is considered a disadvantage of patch-based surgery. [11] In cases where end-to-end anastomosis is difficult due to insufficient carotid artery length, revascularization using autologous or artificial vessel grafts after aneurysm resection is used. [21] Garg et al [2] reported a reconstruction using a saphenous vein rather than an artificial vascular graft.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported details of the surgical maneuver for CEA in other articles. 21 , 22) In terms of using an internal shunt, if SSEP or SSEP+MEP showed a significant change at the time of clamping of the distal ICA, we initially asked the anesthesiologist to elevate systolic ABP up to 20–30% of the preoperative ABP. If the neuromonitor remained unimproved despite this increase in BP, we inserted the internal shunt immediately.…”
Section: Methodsmentioning
confidence: 99%